Sound Insulation of an Acoustic Barrier with Layered Structures of Sonic Crystals – Comparative Studies of Physical and Theoretical Models - Jan RADOSZ (Archives of Acoustics, 2024)
Recent years have seen a growing interest in the potential for the use of sonic crystals as noise barriers. The frequencies with the highest attenuation can be determined by assuming that an integer number of half wavelengths fits the distance between the scatterers. However, this approach limits the usefulness of sonic crystals as a viable noise barrier technology, as it necessitates a significant increase in the overall crystal size to cover a broader frequency range for noise reduction. Based on developed theoretical models, geometrical assumptions were made for the physical models of the acoustic barrier in terms of the materials used and the dimensions of structural elements. Three physical models were developed to verify the design intent. The method involved measuring the transmission loss (TL) and insertion loss (IL) of the sonic crystal structure and comparing these results with theoretical models. The aim of this work was to perform free-field measurements on a real-sized sample in order to verify the strengths and weaknesses of applying layered structures of sonic crystals based on calculations and measurements. The results of the conducted measurements showed satisfactory noise reduction by the developed physical models for key components of the analysed spectrum. It was also demonstrated that layered structures of sonic crystals can achieve greater noise reduction (up to 3.5 dB) and a wider frequency range of attenuation (up to the range of 2000 Hz–5000 Hz) compared to single-layer structures.